Understanding Generation Z: A Decade of Psychological Well-Being Research - Trinanda, Okki; Wardi, Yunia; Evanita, Susi (Universitas Negeri Padang, 2025)
In the past decade, the psychological well-being of Generation Z has gained remarkable attention in Human Resource Management studies. However, the research remains fragmented, leaving significant knowledge gaps. This article aims to consolidate and critically analyze existing literature, providing a systematic review of key themes, methodologies, and findings to guide future research. This study systematically reviewed 332 peer-reviewed publications spanning 2017–2023. The analysis employed referencing network metrics, identified research trends and evaluated methodological strengths and limitations to present a cohesive narrative on Gen Z's psychological well-being. The review reveals a substantial surge in publications, emphasizing Gen Z's mental health challenges and coping mechanisms. However, current studies often focus on favorable variables, lack advanced methodological rigor, and over-rely on cross-sectional designs. This article highlights the need for diversified frameworks, longitudinal approaches, and interdisciplinary collaborations to deepen understanding. As one of the first comprehensive literature reviews on Gen Z's psychological well-being, this article bridges research gaps and offers actionable insights for scholars and practitioners in Human Resource Management and beyond.